Influence of nitrogen fertilisation on the technological quality of wheat - El Chami, Elias; El Chami, Josepha; Tarnawa, Ákos; Kassai, Katalin Mária; Kende, Zoltán; Jolánkai, Márton (Acta Agraria Debreceniensis, 2023)
Wheat is one of the most grown crops around the world. Its primary use is in the production of bread, bakery, and confectionery. The provision of essential nutrients, mainly nitrogen, plays a pivotal role in the growth and development of wheat. The wheat varieties used in the experiment are Alfold and Mv. Menrot. The rates of nitrogen used in the experiment are: 0, 200, 400, 600, 800, and 1000 kg N ha-1. The aim of this study is to evaluate the effect of nitrogen fertilisation on technological quality of wheat and to find the appropriate fertiliser rate to reduce pollution. The results indicate that nitrogen fertilisation did not show a significant effect on thousand kernel weight and test weight. However, nitrogen fertilisation significantly affected protein content, gluten content, Zeleny sedimentation index, and the falling number. The higher the nitrogen fertilisation the better the technological quality parameters of the wheat. The protein content, gluten content, Zeleny sedimentation index and the falling number were the lowest at 0 kg N ha-1 followed by 200 kg N ha-1 then 400 kg N ha-1 and the highest at 600 kg N ha-1.